SOMATIC, AUDITORY, VISUALIZATION, INTELLECTUAL, AND MULTILITERACY MODELS TO INCREASE STUDENTS' INTEREST IN LEARNING - Perawati Bte Abustang; Zuleha; Edwita; Gusti Yarmi (Universitas Majalengka, 2023)
The idea that technology can dramatically change our lives has become a public discourse both within and outside academia. Claims that technology can effect change faster than anything else in human history often convey a sense of urgency that urges us to keep up and inspire fear that parts of our society are being left behind. The cartoon humorously depicts the gap between young people who grew up with technology and older generations who seem mysterious or threatening. Technological change has created a utopian vision of a brave new world, promoting greater equality and active participation. Underlying all these conceptions of modern life is the idea that technological progress creates social changes that require new methods and practices. This study aims to generate interest in learning the social studies model used by Somatic, Auditory, Visualization, Intellectual (SAVI), and Multiliteracy students in SD Negeri 74 Bonti-Bonti students, Maros Regency. The type of research used is action research in the classroom. The subjects in this study were all 4th-grade students who took place at SD Negeri 74 Bonti-Bonti, totaling 25 students consisting of 14 boys and 11 girls. Data collection techniques using observation, questionnaires, and documentation. The research instruments used are observation, questionnaires, and documentation. The results of the study in cycle I showed that students' interest in learning increased with an average score of 63-81 with a percentage of 43% in the interest category. In cycle II, the average interest in learning was 82-100, with a percentage of 60% being very interested. It can be concluded that using the SAVI and Multiliteration models can increase the learning interest of SD Negeri 74 Bonti-Bonti Students, Maros Regency. Gagasan bahwa teknologi dapat mengubah hidup kita secara dramatis telah menjadi wacana publik baik di dalam maupun di luar akademisi. Klaim bahwa teknologi dapat mempengaruhi perubahan lebih cepat daripada apa pun dalam sejarah manusia sering menyampaikan rasa urgensi yang mendesak kita untuk mengikuti dan menimbulkan ketakutan bahwa sebagian masyarakat kita tertinggal. Kartun itu dengan lucu menggambarkan kesenjangan antara anak muda yang tumbuh dengan teknologi dan generasi tua yang tampak misterius atau mengancam. Perubahan teknologi telah membuka visi utopis tentang dunia baru yang berani, mempromosikan kesetaraan yang lebih besar dan partisipasi aktif. Mendasari semua konsepsi kehidupan modern ini adalah gagasan bahwa kemajuan teknologi menciptakan perubahan sosial yang membutuhkan metode dan praktik baru. Penelitian ini bertujuan untuk membangkitkan minat belajar IPS model yang digunakan siswa Somatic, Audiotory, Visualization, Intellectual (SAVI) dan Multiliterasi pada Siswa SD Negeri 74 Bonti-Bonti Kabupaten Maros. Jenis penelitian yang digunakan yaitu Penelitian tindakan di dalam kelas. Subyek dalam penelitian ini adalah seluruh siswa kelas 4 yang bertempat di SD Negeri 74 Bonti-Bonti yang berjumlah 25 Orang siswa yang terdiri dari laki-laki 14 orang dan perempuan 11 orang. Teknik pengumpulan data menggunakan observasi, angket, dan dokumentasi. Instrumen penelitian yang digunakan yaitu menggunakan observasi, angket, dan dokumentasi. Hasil penelitian pada siklus I terdapat minat belajar siswa meningkat dengan nilai rata-rata berada pada 63-81 dengan persentase 43% kategori berminat. Pada siklus II, minat belajar rata-rata berada pada 82-100 dengan persentase 60% kategori sangat berminat. Dapat disimpulkan bahwa dengan menggunakan model SAVI dan Multilterasi dapat meningkatkan minat belajar Siswa SD Negeri 74 Bonti-Bonti Kabupaten Maros.